Public Services to Achieve Good Governance in Indonesia - Ishak, Deding (Jurnal Abdimas Peradaban, 2022)
To meet the various needs of its people, a country will carry out public services so that then goods, services, and various administrative services needed can be fulfilled. This certainly needs to be done because the effectiveness of a government system will be determined mainly by the quality of the implementation of public services from the state to its people. This research will use a qualitative approach with research data sources and previous studies. The study results show that good governance can be achieved through the participation of various holders of positions in government. Then good public service will show that the performance of government management has good quality. The improvements that can be implemented to improve public services include accelerating the formation of public service law, establishing one-stop services, transparency of public service costs, making SOPs, and implementing reforms for employees working in the public service sector.